Early Growth of Cloned Lipote (Syzygium polycephaloides) - Vallesteros, Shierel F.; Banan, Ariel O.; Ibarra, Melanie (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to propagate lipote cuttings through clonal propagation using different growth hormones. The clones were raised in a non-misted closed chamber and transplanted into polyethylene bags for observation of their early growth. The growth performance of the clones was analyzed in terms of height, diameter, leaf number, chlorophyll content, leaf area, shoot biomass, root biomass, and total biomass. After three months, the study was terminated, and analysis of variance showed significant differences in percent survival, chlorophyll content, shoot biomass, and root biomass. Treatment 2, which used a mixture of garden soil and vermicompost at a 1:1 ratio, produced the best results in different growth parameters measurements.